2012
DOI: 10.1002/j.2161-0045.2012.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Developmental Trajectories of Parental Attachment and Career Maturity of South Korean Adolescents

Abstract: This study tested the developmental trajectories of career maturity (CM) and parental attachment (PA), the longitudinal influence of both, and gender as a moderator. Findings showed developmental progressions in adolescents’ PA and CM over 4 years. The change in PA was positively related to the developmental change in CM. For gender, there was a statistically significant difference in the initial status of CM and PA but no significant difference in developmental change. This study verified the longitudinal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
1
21
0
3
Order By: Relevance
“…The existence of a significant relationship between parental attachment and career adaptability is aligned with the research conducted by Choi et al (2012), which states that parental attachment is positively related to career maturity. In addition, the present study is also consistent with research conducted by Salami and Aremu (2007), which revealed that parental attachment is significantly related to career information-seeking behaviour, but, if measured separately, only attachment to the mother has a significant relationship.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The existence of a significant relationship between parental attachment and career adaptability is aligned with the research conducted by Choi et al (2012), which states that parental attachment is positively related to career maturity. In addition, the present study is also consistent with research conducted by Salami and Aremu (2007), which revealed that parental attachment is significantly related to career information-seeking behaviour, but, if measured separately, only attachment to the mother has a significant relationship.…”
Section: Discussionsupporting
confidence: 49%
“…For instance, research conducted by Salami and Aremu (2007) reveals that attachment to the mother is significantly associated with career information-seeking behaviour, whereas attachment to the father is not. In their research about parental attachment and career maturity, Choi et al (2012) show that changes in the quality of parental attachment are positively correlated with changes in career maturity. Another study, by Blustein et al (1995), explains that parental attachment is related to career exploration among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies on career decisiveness have been conducted in the United States or other Western contexts (Choi et al, 2010;Gunkel et al, 2010). In such a situation, a study especially in a collectivist culture needs to be conducted (Choi et al, 2010;Lee, 2007).…”
Section: Identifications Of Gaps In the Literaturementioning
confidence: 98%
“…Studies on change in adolescents' attachment with parents across one‐ to two‐year periods in adolescence indicate that attachment with parents is correlated from one time to the next; however, there is considerable variability in attachment that is not accounted for by earlier attachment (Allen et al., ; Buist, Reitz, & Deković, ; Doyle, Lawford, & Markiewicz, ; Pierce & Lydon, ). Studies on the long‐term stability of parental attachment (four or more years) show mixed findings, with some indicating substantial change (e.g., Aikins et al., ; Beijersbergen, Juffer, Bakermans‐Kranenburg, & Van IJzendoorn, ; Choi, Hutchison, Lemberger, & Pope, ; Weinfield, Sroufe, & Egeland, ; Weinfield, Whaley, & Egeland, ) and some indicating considerable stability over time (e.g., Ammaniti et al., ; Hamilton, ; Waters, Merrick, Treboux, Crowell, & Albersheim, ).…”
Section: To What Extent Does Attachment Security Change During Adolesmentioning
confidence: 99%
“…Effects of gender on attachment relationships in adolescence often suggest that females report more attachment security with mothers and fathers than males during adolescence (Buist et al., ; Choi et al., ). However, research does not always find a relationship between gender and attachment.…”
Section: To What Extent Does Attachment Security Change During Adolesmentioning
confidence: 99%